Adhesive hydrogel for oral periodontal tissue regeneration and preparation method thereof
Adhesive hydrogels prepared with raw materials such as gelatin and dopamine have solved the problem of poor effectiveness of existing tissue adhesives in hard tissue applications, and achieved efficient bonding and cell growth support in oral periodontal tissue regeneration.
Patent Information
- Application Number
- CN202411856231.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-17
AI Technical Summary
Existing tissue adhesives have limitations in adhesion, biosafety, mechanical properties and functions, especially in hard tissue applications.
By using raw materials such as gelatin and dopamine, combined with hydrogen bonds and reacting with amide, an adhesion hydrogel with high porosity and connecting pores is prepared, which is suitable for oral periodontal tissue regeneration.
The adhesion hydrogel has good adhesion on the wet soft and hard tissue surfaces. After complete water absorption and swelling, it provides a porous structure suitable for cell growth and tissue regeneration, making up for the disadvantage that existing filling materials are difficult to fix.
Smart Images

Figure CN119656365A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of tissue engineering materials, and in particular to an adhesive hydrogel for oral periodontal tissue regeneration and a preparation method thereof. Background Art
[0002] Tissue adhesives have been widely studied recently. They have more clinical advantages than surgical sutures, are easy to operate, and have good sealing properties. However, existing liquid or hydrogel tissue adhesives have some limitations, such as weak adhesion, low biosafety, poor mechanical properties, and single functions. Moreover, these studies are often limited to the connection of soft tissues, such as skin and internal organs, and rarely applied to hard tissues.
[0003] The succinimidyl ester groups grafted onto gelatin-based cross-linked polyacrylic acid polymers can form covalent cross-links with the amino groups in the collagen matrix to increase the bonding affinity. The catechol groups of dopamine also have high reactivity by simulating the structure of the adhesive amino acid 3,4-dihydroxyphenylalanine in mussel adhesive protein. A large number of medical tissue adhesives modified by them can firmly adhere to various polymer materials, metal materials and biological tissue surfaces.
[0004] In the current literature, the porosity and pore size of the prepared tissue adhesives are low, which cannot meet the requirements of ideal scaffolds for tissue regeneration. Kai Chen (Kai Chen. Advanced Functional Materials. 2023, 33, 2303836) et al. developed a polyethylene glycol adhesive by acrylation of polyethylene glycol. The porosity and pore size are low, and it hardly absorbs water and swells. Moreover, its adhesion on the surface of soft tissue was only tested. Summary of the invention
[0005] The purpose of the present invention is to provide an adhesive hydrogel for oral periodontal tissue regeneration and a preparation method thereof in view of the deficiencies of the prior art. The prepared adhesive hydrogel has good tissue adhesion and can be tightly bonded to the moist soft and hard tissue surfaces, making up for the shortcoming that oral periodontal filling materials are difficult to fix in clinical practice. The adhesive hydrogel has a high porosity after being completely swollen by water, and the pores on its surface and inside are interconnected, so that it can provide more space for the growth of oral periodontal tissue, which is suitable for cell growth and regeneration of oral periodontal tissue.
[0006] Another object of the present invention is to provide a method for preparing the oral periodontal tissue engineering scaffold.
[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0008] An adhesive hydrogel for oral periodontal tissue regeneration, the adhesive hydrogel is a porous scaffold with good tissue adhesion on wet soft and hard tissue surfaces, and the pores on the surface and inside are interconnected after swelling with water absorption, the porosity is 75.28-89.73%, and the pore size is 43-157μm.
[0009] Furthermore, the adhesive hydrogel wet-bonds to a variety of tissues or materials through hydrogen bonding and amide reactions.
[0010] A method for preparing an adhesive hydrogel for oral periodontal tissue regeneration, the preparation method comprising the following steps:
[0011] Step (1) dissolving gelatin in deionized water and heating at 60° C. to completely dissolve the gelatin to obtain a first mixed solution;
[0012] Step (2) adding dopamine powder to the first mixed solution, stirring for 2 minutes in a dark environment to allow the mixture to fully crosslink, thereby obtaining a second mixed solution;
[0013] Step (3) adding sodium hydroxide solution to the second mixed solution and stirring for 10 minutes to oxidize dopamine to obtain a third mixed solution;
[0014] Step (4) adding acrylic acid, methacrylate gelatin, acrylic acid N-hydroxysuccinimide ester, and α-ketoglutaric acid to the third mixed solution obtained in step (3) and stirring to obtain a fourth mixed solution;
[0015] Step (5) adding nano-hydroxyapatite to the fourth mixed solution obtained in step (4) and stirring to obtain a fifth mixed solution;
[0016] Step (6) degassing the fifth mixed solution obtained in step (5) and adding it into a quartz mold for ultraviolet light crosslinking. After completely drying, the desired adhesive hydrogel is obtained.
[0017] Furthermore, the gelatin in step (1) is type A gelatin with a jelly strength of 300, the jelly strength of GelMA is 90-100, and the extraction degree is 60%.
[0018] Furthermore, the first mixed solution in step (1) is a 20 wt % gelatin aqueous solution.
[0019] Furthermore, the dopamine powder in step (2) is 1% of the mass of gelatin, the temperature is 60° C., the stirring time is 2 min, and the rotation speed is 100 r / min.
[0020] Furthermore, the sodium hydroxide solution in step (3) is a 0.1N standard solution, and the volume ratio of the sodium hydroxide solution added to the second mixed solution is 1:1. The stirring temperature is 25° C., the stirring time is 10 min, and the rotation speed is 100 r / min.
[0021] Furthermore, in step (4), the concentration of acrylic acid is 3 wt %, the concentrations of methacrylate gelatin, acrylic acid N-hydroxysuccinimide ester, and α-ketoglutaric acid are 0.1 wt %, 1 wt %, and 0.3 wt %, respectively, the stirring time is 5 min, and the rotation speed is 200 r / min.
[0022] Furthermore, in step (5), the diameter of the nano-hydroxyapatite is less than 200 nm, the concentration is 1.5 wt %, the stirring time is 5 min, and the rotation speed is 200 r / min.
[0023] Furthermore, in step (6), the wavelength of the ultraviolet light is 360 nm, the power is 20 W, and the cross-linking time is 1 h.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] The adhesive hydrogel prepared by the photocrosslinking method under the synergistic effect of specific concentrations and proportions has good tissue adhesion and high porosity after complete water absorption and swelling. The pores on the surface and inside are interconnected, which is beneficial to the growth of cells and tissues, the transmission of oxygen and nutrients, and the discharge of metabolic products.
[0026] The adhesive hydrogel of the present invention is a solid adhesive tape, which is easy to cut and use, and can meet the bonding needs of irregular shapes in clinical practice.
[0027] The porous structure in the adhesive hydrogel of the present invention enables it to have a larger specific surface area, and the pores are interconnected, which is conducive to the growth of cells toward the inside.
[0028] The adhesive hydrogel of the present invention has a high porosity after completely absorbing water and swelling, and the porosity can be as high as 75.28-89.73%. The pore size is 43-157 μm, which provides favorable conditions for the growth of cells and oral periodontal tissues and is conducive to the growth of cells and oral periodontal tissues. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a field emission scanning electron microscope picture of the adhesive hydrogel of the present invention.
[0030] Figure 2 It is the infrared spectrum analysis diagram of the adhesive hydrogel of the present invention.
[0031] Figure 3 This is a field emission scanning electron microscope picture of the adhesive hydrogel of the present invention after being inoculated with bone marrow mesenchymal stem cells for one week. DETAILED DESCRIPTION
[0032] In order to better understand the technical content of the present invention, specific embodiments are given and described as follows in conjunction with the accompanying drawings.
[0033] An adhesive hydrogel for oral periodontal tissue regeneration, the adhesive hydrogel is a porous scaffold with good tissue adhesion on wet soft and hard tissue surfaces, and the pores on the surface and inside are interconnected after swelling with water, the porosity is 75.28-89.73%, and the pore size is 43-157 μm. The adhesive hydrogel wet-bonds with various tissues or materials through hydrogen bonding and amide reaction.
[0034] A method for preparing an adhesive hydrogel for oral periodontal tissue regeneration, the preparation method comprising the following steps:
[0035] Step (1) dissolving gelatin in deionized water, heating at 60°C to completely dissolve it, and obtaining a first mixed solution; the gelatin is type A gelatin with a jelly strength of 300, and GelMA has a jelly strength of 90-100 and an extraction degree of 60%. The first mixed solution is a 20wt% gelatin aqueous solution.
[0036] Step (2) adding dopamine powder to the first mixed solution, stirring for 2 minutes in a dark environment to fully crosslink the solution, and obtaining a second mixed solution; the dopamine powder is 1% of the gelatin mass, the temperature is 60° C., the stirring time is 2 minutes, and the rotation speed is 100 r / min.
[0037] Step (3) adding sodium hydroxide solution to the second mixed solution, stirring for 10 minutes to oxidize dopamine, and obtaining a third mixed solution; the sodium hydroxide solution is a 0.1N standard solution, and the volume ratio of the sodium hydroxide solution to the second mixed solution is 1:1, the stirring temperature is 25° C., the stirring time is 10 minutes, and the rotation speed is 100 r / min.
[0038] Step (4) adding acrylic acid, methacrylate gelatin, acrylic acid N-hydroxysuccinimide ester and α-ketoglutaric acid to the third mixed solution obtained in step (3) and stirring to obtain a fourth mixed solution; the concentration of acrylic acid is 3wt%, the concentrations of methacrylate gelatin, acrylic acid N-hydroxysuccinimide ester and α-ketoglutaric acid are 0.1wt%, 1wt% and 0.3wt% respectively, the stirring time is 5min, and the rotation speed is 200r / min.
[0039] Step (5) adding nano-hydroxyapatite to the fourth mixed solution obtained in step (4) and stirring to obtain a fifth mixed solution; the diameter of the nano-hydroxyapatite is less than 200nm, the concentration is 1.5wt%, the stirring time is 5min, and the rotation speed is 200r / min.
[0040] Step (6) Degas the fifth mixed solution obtained in step (5) and add it into a quartz mold for ultraviolet crosslinking. After complete drying, the desired adhesive hydrogel is obtained. The ultraviolet wavelength is 360nm, the power is 20W, and the crosslinking time is 1h.
[0041] The gelatin, dopamine, sodium hydroxide, acrylic acid, methacrylate gelatin, acrylic acid N-hydroxysuccinimide ester, α-ketoglutaric acid, and nano-hydroxyapatite used in the following examples were all purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. The gelatin was type A gelatin with a jelly strength of 300, the GelMA had a jelly strength of 90-100, an extraction degree of 60%, and the diameter of the nano-hydroxyapatite was <200 nm.
[0042]
preparation
[0043] The preparation methods of the following examples are all prepared by the same method, namely:
[0044] Step (1) dissolving gelatin in deionized water and heating at 60° C. to completely dissolve the gelatin to obtain a first mixed solution;
[0045] Step (2) adding dopamine powder to the first mixed solution, stirring for 2 minutes in a dark environment to allow the mixture to fully crosslink, thereby obtaining a second mixed solution;
[0046] Step (3) adding sodium hydroxide solution to the second mixed solution and stirring for 10 minutes to oxidize dopamine to obtain a third mixed solution;
[0047] Step (4) adding acrylic acid, methacrylate gelatin, acrylic acid N-hydroxysuccinimide ester, and α-ketoglutaric acid to the third mixed solution obtained in step (3) and stirring to obtain a fourth mixed solution;
[0048] Step (5) adding nano-hydroxyapatite to the fourth mixed solution obtained in step (4) and stirring to obtain a fifth mixed solution;
[0049] Step (6) degassing the fifth mixed solution obtained in step (5) and adding it into a quartz mold for ultraviolet light crosslinking. After completely drying, the desired adhesive hydrogel is obtained.
[0050] The variables in the preparation process of Example 1 to Example 10 are shown in Table 1:
[0051] Table 1
[0052]
[0053]
Characterization
[0054] like Figure 1 This is a field emission scanning electron microscope photograph of the prepared adhesive hydrogel, which shows that it contains a porous structure and the pores are interconnected.
[0055] The porosity of the adhesive hydrogels prepared in Examples 1 to 10 was measured using a pressure pump instrument, and the pore size of the adhesive hydrogels was detected by taking photos using a microscope. The results are shown in Table 2:
[0056] Table 2
[0057]
[0058]
[0059] As can be seen from Table 2, the adhesive hydrogel prepared by the synergistic effect of specific concentration ratio and reaction time has a high porosity and a large pore size. The porosity can reach up to 89.73%, the pore size can be up to 157 μm, and the pore size distribution greater than 50 μm is as high as 95%, providing favorable conditions for the growth of cells and oral periodontal tissues.
[0060]
Application Test
[0061] 1. Fourier infrared spectroscopy test
[0062] The adhesive hydrogel prepared in Example 2 was completely dried and then tested under a Fourier infrared spectrometer.
[0063] like Figure 2 This is the infrared spectrum analysis chart of the adhesive hydrogel. It can be seen that 3319.40cm-1 is the stretching vibration absorption peak of OH, 2925.23cm-1 is the stretching vibration absorption peak of CH, 1702.69cm-1 is the stretching vibration absorption peak of ester group C=O, 1629.38cm-1 is the stretching vibration of C=O (amide I band), 1538.89cm-1 is the skeleton vibration absorption peak of benzene ring, 1448.9cm-1 is the bending vibration absorption peak of -CH2-, 1408.89cm-1 is the stretching vibration of CN (amide III band), 1162.65cm-1 is the stretching vibration absorption peak of CO, 1032.14cm-1 is the in-plane bending vibration absorption peak of CH, and 797.51cm-1 is the out-of-plane bending vibration absorption peak of CH, indicating that the hydrogel is bonded to various tissues or materials through hydrogen bonds and amide reactions.
[0064] 2. Cell Adhesion Test
[0065] The adhesive hydrogel prepared in Example 2 was transferred to a 24-well cell culture plate, and 2×10 oral periodontal mesenchymal stem cells were inoculated into each well. 4After culturing for one week, the cells were fixed with 2.5% glutaraldehyde for 30 min, dehydrated with 30%, 50%, 70%, and 90% ethanol gradient, and then dehydrated with anhydrous ethanol three times, dried, sprayed with gold, and photographed under a field emission scanning electron microscope.
[0066] like Figure 3 This is a field emission scanning electron microscopy image of oral periodontal mesenchymal stem cells inoculated in adhesive hydrogel one week later. It was found that the cells can adhere and grow on the surface of the hydrogel (indicated by the white arrow), indicating that the adhesive hydrogel has good cell compatibility.
[0067] The present invention discloses an adhesive hydrogel for oral periodontal tissue regeneration and a preparation method thereof. The adhesive hydrogel is prepared by using gelatin and polyacrylic acid as main raw materials and based on a photocrosslinking method; the adhesive hydrogel has good tissue adhesion and can be tightly bonded to moist soft and hard tissue surfaces, making up for the shortcoming that oral periodontal filling materials are difficult to fix in clinical practice. The adhesive hydrogel has a high porosity after being completely swollen by water, and the pores on its surface and inside are interconnected, so that it can provide more space for the growth of oral periodontal tissue, which is suitable for cell growth and regeneration of oral periodontal tissue.
[0068] Although the present invention has been disclosed as above with preferred embodiments, it is not intended to limit the present invention. A person with ordinary knowledge in the technical field to which the present invention belongs may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be determined by the definition of the claims.
Claims
1. An adhesive hydrogel for oral periodontal tissue regeneration, characterized in that: The adhesive hydrogel is a porous scaffold with tissue adhesion on wet soft and hard tissue surfaces, and the pores on the surface and inside are interconnected after swelling with water absorption, with a porosity of 75.28-89.73% and a pore size of 43-157 μm.
2. The adhesive hydrogel for oral periodontal tissue regeneration according to claim 1, characterized in that: The adhesive hydrogel wet bonds to tissue or materials through hydrogen bonding and amide reactions.
3. A method for preparing the adhesive hydrogel for oral periodontal tissue regeneration according to any one of claims 1 to 2, characterized in that: The preparation method comprises the following steps: Step (1) dissolving gelatin in deionized water and heating at 60° C. to completely dissolve the gelatin to obtain a first mixed solution; Step (2) adding dopamine powder to the first mixed solution, stirring for 2 minutes in a dark environment to allow the mixture to fully crosslink, thereby obtaining a second mixed solution; Step (3) adding sodium hydroxide solution to the second mixed solution and stirring for 10 minutes to oxidize dopamine to obtain a third mixed solution; Step (4) adding acrylic acid, methacrylate gelatin, acrylic acid N-hydroxysuccinimide ester, and α-ketoglutaric acid to the third mixed solution obtained in step (3) and stirring to obtain a fourth mixed solution; Step (5) adding nano-hydroxyapatite to the fourth mixed solution obtained in step (4) and stirring to obtain a fifth mixed solution; Step (6) degassing the fifth mixed solution obtained in step (5) and adding it into a quartz mold for ultraviolet light crosslinking. After completely drying, the desired adhesive hydrogel is obtained.
4. The method for preparing the adhesive hydrogel for oral periodontal tissue regeneration according to claim 3, characterized in that: The gelatin in step (1) is type A gelatin with a jelly strength of 300, the jelly strength of GelMA is 90-100, and the extraction degree is 60%.
5. The method for preparing the adhesive hydrogel for oral periodontal tissue regeneration according to claim 3, characterized in that: The first mixed solution described in step (1) is a 20wt% gelatin aqueous solution.
6. The method for preparing the adhesive hydrogel for oral periodontal tissue regeneration according to claim 3, characterized in that: The dopamine powder described in step (2) is 1% of the gelatin mass, the temperature is 60° C., the stirring time is 2 minutes, and the rotation speed is 100 r / min.
7. The method for preparing the adhesive hydrogel for oral periodontal tissue regeneration according to claim 3, characterized in that: The sodium hydroxide solution in step (3) is a 0.1N standard solution, and the volume ratio of the sodium hydroxide solution added to the second mixed solution is 1:
1. The stirring temperature is 25° C., the stirring time is 10 min, and the rotation speed is 100 r / min.
8. The method for preparing the adhesive hydrogel for oral periodontal tissue regeneration according to claim 3, characterized in that: The concentration of acrylic acid in step (4) is 3wt%, the concentrations of methacrylate gelatin, acrylic acid N-hydroxysuccinimide ester, and α-ketoglutaric acid are 0.1wt%, 1wt%, and 0.3wt%, respectively. The stirring time is 5min and the rotation speed is 200r / min.
9. The method for preparing the adhesive hydrogel for oral periodontal tissue regeneration according to claim 3, characterized in that: The nano-hydroxyapatite described in step (5) has a diameter of less than 200 nm, a concentration of 1.5 wt %, a stirring time of 5 min, and a rotation speed of 200 r / min.
10. The method for preparing the adhesive hydrogel for oral periodontal tissue regeneration according to claim 3, characterized in that: The ultraviolet light wavelength described in step (6) is 360nm, the power is 20W, and the cross-linking time is 1h.
Citation Information
Patent Citations
Electrospinning PLGA / PCL fiber membrane composite chitosan sponge stent for oral cavity alveolar bone regeneration and preparation method thereof
CN112972777A
Preparation method of continuous adhesion hydrogel, hydrogel obtained by preparation method and application of hydrogel
CN113637186A
Dry double-sided material for bonding wet tissues and devices
CN114173832A
Semi-synthetic tissue constructs for tissue regeneration
US20190351100A1
Biodegradable system for regenerating the periodontium
US5077049A
Cited By
Oligopeptide gel carrier structure for periodontal recovery as well as preparation method and application of oligopeptide gel carrier structure
CN120168402A
Polylysine-conjugated nanohydroxyapatite linked with alpha-ketoglutarate and its applications
TWI924567B